Are Junior Residents Accurate at Predicting Fetal Weight? An Analysis of Junior Residents' Performance of Estimated Fetal Weight Using Ultrasound and Leopold's Maneuver - Kimberly Huynh; Alicia Lunardhi; Karren Lewis; Trevor Pickering; Hindi E. Stohl (Women's Health Reports, 2024)
Background: Performing accurate estimated fetal weights (EFWs) is a critical skill developed in obstetrics residency training. Resident physicians are often the first to perform EFWs on obstetric patients when they enter care. Evaluating residents' accuracy in performing EFWs is crucial for assessing their achievement in residency training milestones and providing patient care. Methods: As part of an educational initiative program between 2014 and 2020, postgraduate year 1 (PGY1) and postgraduate year 2 (PGY2) residents performed EFW measurements on 10 term (>37w0d) patients using ultrasound and Leopold's maneuver and 10 preterm (>24w0d and <37w0d) patients using ultrasound. Clinical characteristics, mode of delivery, and actual birthweights (BWs) were recorded for each patient. The accuracy of these estimates was evaluated using mixed-effect regression models. Results: Thirty-three residents, 1127 deliveries, and 1790 EFW measurements were evaluated. Overall, the percentage of residents with estimations within 10% of actual BW went up in PGY2 for Leopold's and ultrasound term births, but not for preterm ultrasound births. Maternal body mass index and actual BW were associated with absolute percentage estimation error. After adjusting for these variables, there was a statistically significant decrease in error between PGY1 and PGY2 for Leopold's method in term births; ultrasound (term and preterm) showed more modest reductions in error during PGY2. Discussion: Resident physicians have accurate estimates of EFWs early in their training, beginning in their first year of residency by both Leopold's maneuver and ultrasound. Furthermore, PGY2 residents performed better than PGY1 residents for Leopold's method.